2018
DOI: 10.1007/s12630-018-1065-7
|View full text |Cite|
|
Sign up to set email alerts
|

Intraoperative cerebral oximetry-based management for optimizing perioperative outcomes: a meta-analysis of randomized controlled trials

Abstract: Intraoperative cerebral oximetry appears to be associated with a reduction in POCD, although this result should be interpreted with caution given the significant heterogeneity in the studies examined. Further large (ideally multicentre) RCTs are needed to clarify whether POCD can be favourably impacted by the use of cerebral oximetry-guided management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 62 publications
(85 reference statements)
2
29
1
1
Order By: Relevance
“…These studies mainly report a beneficial effect of the intervention algorithm in relation to cerebral desaturation measured with NIRS, yet conflicting results have been reported in relation to the effect on POCD, 17e21 which has also been summarised in recent meta-analyses. 5,7,8 Other studies investigated the association between rScO 2 and POCD by comparing NIRS values between patients with and without POCD after cardiac surgery 2,3,22,23 in order to Table 3 Regional cerebral oxygen saturation (rScO 2 ) values for cardiac surgery patients with and without postoperative cognitive dysfunction (POCD) at discharge and at 3 monthsdhigh target MAP group. Median with (inter-quartile range) and tested with ManneWhitney U-test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies mainly report a beneficial effect of the intervention algorithm in relation to cerebral desaturation measured with NIRS, yet conflicting results have been reported in relation to the effect on POCD, 17e21 which has also been summarised in recent meta-analyses. 5,7,8 Other studies investigated the association between rScO 2 and POCD by comparing NIRS values between patients with and without POCD after cardiac surgery 2,3,22,23 in order to Table 3 Regional cerebral oxygen saturation (rScO 2 ) values for cardiac surgery patients with and without postoperative cognitive dysfunction (POCD) at discharge and at 3 monthsdhigh target MAP group. Median with (inter-quartile range) and tested with ManneWhitney U-test.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a decrease in the severity, frequency, and accumulated load of cerebral desaturation when applying the intervention algorithm, but the effect on POCD occurrence is inconsistent among studies. 5,7,8 This may either be related to the fact that the interventions used to prevent cerebral desaturation are not sufficient or alternatively, that the association between rScO 2 readings and POCD is weak. In the Perfusion Pressure Cerebral Infarct (PPCI) trial, neurological complications were studied in patients randomised to two distinct BP targets during on-pump cardiac surgery.…”
mentioning
confidence: 99%
“…We read with interest the meta-analysis regarding intraoperative cerebral oximetry-based monitoring for maximizing perioperative outcomes by Zorrilla-Vaca et al 1 We note, however, some important discrepancies between the original source literature and the data that are used in the current analysis, which raise concerns. While conclusions regarding the primary outcome of cognitive impairment are not impacted, the means to reach that conclusion are at times not as accurate as they could be, and some of the secondary outcome conclusions differ in significance.…”
Section: To the Editormentioning
confidence: 96%
“…These relatively longer-term postoperative PND end points are consistent with the latest nomenclature guidelines that have been promulgated in an attempt to bring better consistency and reliability to studies of PND. 2,3 Indeed, although recent meta-analyses have suggested a potential relationship between intraoperative management guided by cerebral oximetry and a reduction in cognitive dysfunction, 4 the frequent variability in defining these cognitive changes (both in terms of cognitive domains that are being measured and the time points at which the assessments are made) brings considerable heterogeneity to the subject.…”
mentioning
confidence: 99%